Pemetaan Potensi Bahan Baku Teh Herbal di Lahan Hutan Garapan Gapoktanhut Puncak Semaring Desa Mekar Sari Kabupaten Lombok Timur - Wangiyana, I Gde Adi Suryawan; Gunawan, Frendi; Triandini, I Gusti Agung Ayu Hari (Fakultas Kehutanan, Universitas Hasanuddin, 2023)
This study aims to carry herbal tea resources mapping on the community forest of Gapoktanhut Puncak Semaring at Mekar Sari Village. There are three steps in this study. The first step is mapping the forest using Locus-GIS application. The second step is herbal tea resources observation. The third step is Gapoktanhut member interview about herbal tea plant resources utilization on their forest. Based on the observation, 13 species of herbal tea resources have been found in four regions of the Gapoktanhut Society forest. These species are pandan, curcuma, cinnamon, cocoa, lemongrass, galangal, clove, ginger, betel, coffee, avocado, and strobilanthes. Ginger and curcuma are the only species that have been utilized as an herbal drinks. The other species have been utilized as a seasoning, traditional medicine, animal feed, and plant fence. It could be concluded that Gapoktanhut Puncak Semaring has a potential herbal tea resources species but only utilized 15% of them.